(I)由题意知
2 b n 2 = a n + a n+1
a n+1 2 = b n 2 • b n+1 2 ,
又∵数列a n、b n各项都是正数,∴a n+1=b nb n+1,则a n=b n-1b n
代入2b n 2=a n+a n+1,得2b n 2=b n-1b n+b nb n+1
即2b n=b n-1+b n+1,所以数列b n是等差数列.
(II)∵a 1=2,a 2=6,又2b n 2=a n+a n+1,得2b 1 2=a 1+a 2=8,解得b 1=2
又∵a 2=b 1b 2=6∴b 2=3,由(I)知数列b n是等差数列,则公差d=b 2-b 1=1
∴b n=b 1+(n-1)d=2+n-1=n+1,
又a n=b n-1b n,得a n=n(n+1)=n 2+n,
∴ c n =( a n - n 2 )• q b n =n q n+1 ,
则当q=1时,c n=n,此时 S n =
n(n+1)
2 ;
当q≠1时,S n=c 1+c 2++c n=1×q 2+2×q 3++nq n+1,①
所以qS n=qc 1+qc 2++qc n=1×q 3+2×q 4++nq n+2②
由①-②,得 (1-q) S n = q 2 + q 3 + q n+1 -n q n+2 =
q 2 (1- q n )
1-q -n q n+2 ,
即 S n =
q 2 (1- q n )
(1-q) 2 -
n q n+2
1-q
综上可知, S n =
n(n+1)
2 ,(q=1)
q 2 (1- q n )
(1-q) 2 -
n q n+2
1-q ,(q≠1)